EVALUATION OF LOCAL PUBLIC SERVICE AGENCY FINANCIAL MANAGEMENT PATTERN (PPK-BLUD) IMPLEMENTATION AT PUSKESMAS IN KARANGANYAR REGENCY - Sutaryo, Sutaryo; Arifin, Taufiq; Aryani, Y Anni; Rahmawati, Isna Putri; Nurrahmawati, An (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to evaluate the implementation of the Local Public Service Agency Financial Management Pattern (PPK-BLUD) at Community Health Center (Puskesmas) in Karanganyar Regency. This research uses secondary data from documentation of local financial management regulations, organizational structure and profile of BLUD, financial management documents, unaudited and audited financial reports, as well as management letters from the audit of BLUD financial statement. Our analysis was carried out with an in-depth overview of PPK-BLUD implementation that has been running until 2023 and evaluating its implementation based on the applicable regulations and best business practices. This research found that the implementation of PPK-BLUD at Puskesmas in Karanganyar Regency has been implemented quite well in terms of legality, human resources, and the BLUD financial management process. However, there are still several limitations in terms of human resources competency in the financial sector, there are no technical regulations, and coordination and review are not yet optimal. Due to the limitations still being faced, the BLUD Puskesmas in Karanganyar Regency is recommended to develop technical regulations for BLUD financial management guidelines, increase human resources and/or provide adequate training, as well as improve coordination, monitoring and review with vertical agencies. Finally, it can be expected that the implementation of PPK-BLUD will be more established, orderly, and accountable.